ByLimb: Development of a New Technique to Implant Intracorneal Ring-Segments from the Perilimbal Region - Roberto Albertazzi; Roger Zaldivar; Carlos Rocha-de-Lossada (Life, 2023)
A new technique that allows implanting intracorneal ring-segments (ICRS) from the limbal zone is described. Using a femtosecond laser (FSL), a 360° corneal tunnel is created with an internal diameter of 5.4 mm and an external diameter of 7.0 mm, with a wider area (0.2 mm inner and 0.2 mm outer) in the upper 60° of the tunnel (called landing zone). Next, a 4.36 mm-long corneal-limbal incision was created with the FSL, which connects to the bubbles created in the landing zone. The entire procedure was performed using intraoperative optical coherence tomography (OCT). Once the two incisions were connected using blunt-edged Mac Pherson forceps, the bubbles were released from the surgical plane. The programmed ICRS(s), 6 mm in diameter, are then placed in the corneal tunnel from the limbal incision with the aid of Sinskey forceps. Finally, when the ICRS is in place, the surgery is complete.